Molecular divergence of locally grown pumpkin (Cucurbita maxima) cultivars through some isozyme tests - Haque, ME; Islam, MA; Sikdar, B (Journal of Bio-Science, 2012)
Context: Pumpkin (Cucurbita maxima) is highly polymorphic vegetable species and its polymorphism can be analyzed by isozyme molecular marker. Objective: To analyze genetic polymorphism among 10 locally grown pumpkin cultivars by isozyme. Materials and Methods: Fresh leaves of young plant of different cultivars were used for enzyme extraction. Enzyme extracts were prepared by homogenizing of 2 g sample of each cultivar. Prechilled mortar and pestle nestled in ice along with 1% polyvinylpyrrolidone and 2 ml of chilled extraction buffer were used prior to centrifuge. N-PAGE was conducted for different isozymes and stained the gels with specific chemicals for band development. Results: Five isozymes (peroxidase, esterase, acid phosphatase, alkaline phosphatase and malate dehydrogenase) were tested for genetic polymorphism analysis of pumpkin cultivars. Among them esterase, peroxidase and alkaline phosphatase showed polymorphism in different cultivars with 75-, 58.33- and 41.18% respectively. But acid phosphatase and malate dehydrogenase did not show any polymorphism. Esterase and peroxidase produced band quickly than others. Relative mobility of first band of esterase, peroxidase, acid phosphatase, alkaline phosphatase and malate deghdrogenase was 0.063, 0.045, 0.262, 0.07 and 0.093 respectively Conclusion: Out of five isozymes, effective polymorphism was found in esterase and peroxidase test DOI: http://dx.doi.org/10.3329/jbs.v19i0.13006 J. bio-sci. 19 89-93, 2011